A Robust Control for an Aerial Robot Quadrotor under Wind Gusts - Li Ding; Zhenwei Wang (Journal of Robotics)
A robust flight controller based on linear active disturbance rejection control (LADRC) is proposed for stability control of an aerial robot quadrotor under wind gusts. The nonlinear dynamical model of the quadrotor, considering the wind disturbance, is firstly established through Newton-Euler method. Subsequently, a robust LADRC technique is proposed to design the controllers for the inner loop and outer loop of the aircraft. In this control scheme, the linear extended state observer (LESO) serves as a compensator which can effectively reject the wind gusts. Then, a method of parameter tuning is introduced to obtain the optimized control performance. Finally, the effectiveness and advantages of the proposed controller are demonstrated through series of simulation case.